Problemas e problematização no Ensino de Química: um estudo com graduandos de universidades do Oeste do Paraná - Mori, Lorraine (2019)
In general, problems can be characterized as activities articulated among themselves, in a problematic context that obliges students to use knowledge already acquired for the construction of scientific knowledge, removing them from passivity during the learning process. This work has as its theme the discussion about problems and problematization in the Teaching of Chemistry, with the objective of understanding the knowledge of graduates of Chemistry Licenciatura of universities located in the Western region of Paraná, Brazil, about problems and problematization and how they are being prepared for the teaching profession. For this, our investigation refers to the understanding that the undergraduate students of chemistry have basic orientation in the initial formation (undergraduate) for the use of problems and problematization in didactic activities as teachers. We used the approach of qualitative research and data construction took place through semi-structured interviews with academics during curricular internship classes and didactic construction and problem solving activities carried out by academics. Graduating students of the Chemistry Degree course of two public universities located in the western region of the state of Paraná were interviewed. For the analysis of the data, we take elements of the discourse analysis proposed by Orlandi and construct narratives to present the moments of dialogue established during the interview. The problems elaborated and the proposal for their resolution were made considering assumptions and criteria present in the literature on the subject. Given our results, we observed that the interviewees know problems and the activity of problematizing in a superficial way, presenting elements very close to the proposal of the "Three pedagogical moments". On the ability of these academics to elaborate and solve problems, we can say that they lack knowledge about the different methodologies that make use of problems for the construction of scientific knowledge on the part of the students. We point out as a way the introduction of themes in activities to be carried out with undergraduates such as: Problem-Based Learning, Problem Solving, Generating Theme, Three Pedagogical Moments, Study Situations, Case Studies, Research Teaching, Islands of Rationality and Methodology because we understand that if the teacher has more knowledge about methodologies that make use of problems in their constitution, they will have a higher condition of proposing problematizing activities in chemistry classes in the school.